2018
DOI: 10.1186/s12889-018-6041-1
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and barriers associated with seasonal influenza vaccination uptake among public health students; a cross-sectional study

Abstract: BackgroundAlthough research has explored influenza vaccination uptake among medical and college students, there is a dearth of research in understanding influenza vaccination uptake and attitudes toward the vaccine among future public health practitioners. Undergraduate public health students represent future public health practitioners who may be a significant educational resource for health information, including the importance of vaccinations.MethodsThis cross-sectional study utilized survey data from 158 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 34 publications
8
61
3
Order By: Relevance
“…Making the vaccination compulsory increases vaccination coverage among healthcare students [39,41]. These determinants of vaccination i.e., freshman and medical student, are not translatable to all related studies, but our findings were similar to those in previous studies [35,41,[47][48][49].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Making the vaccination compulsory increases vaccination coverage among healthcare students [39,41]. These determinants of vaccination i.e., freshman and medical student, are not translatable to all related studies, but our findings were similar to those in previous studies [35,41,[47][48][49].…”
Section: Discussionsupporting
confidence: 88%
“…It is also true that freshmen in medicine and healthcare faculties have very little chance to interact with patients, not motivating them for vaccination. The estimated coverage among students in medicine and healthcare faculties was lower but comparable to that in Australia (53.8%) [41] and similar to the rate in Southern California (43.0%) [35]. Making the vaccination compulsory increases vaccination coverage among healthcare students [39,41].…”
Section: Discussionmentioning
confidence: 71%
“…However, not all students with health-related majors view influenza vaccination positively. Rogers et al (2018) found that 49.4% of undergraduate public health students who did not receive the flu vaccination believed that administration could cause the flu, and 30.4% were concerned about adverse side effects.…”
Section: College Students' Perception Of Influenza Vaccinationmentioning
confidence: 99%
“…These results were not exactly congruent with the literature review (see Figure 1). Rogers et al (2018) found that a significant number of students were concerned about the side effects of influenza vaccines. However, concern for the possible side effects of influenza vaccination was not a top theme in this study.…”
Section: What Are College Students' Perceptions Of Influenza Vaccinatmentioning
confidence: 99%
See 1 more Smart Citation